A erotomania como resposta psicótica aos impasses do amor - Juliana Bressanelli (2007)
This work of dissertation consists of approaching the concept of Erotomania as a response given by the psychotic for the question that is presented to the human being, caused by the contingency inherent to the encounter with the loving partner. We establish how love sets up a problem to the human being and we work this perspective pointing the specificity of Erotomania in its differentiation with the response given by the neurotic, which is, the loving transference. We present two clinical cases that allow us to exemplify and to oppose these two types of response. Considerations are also made referring to the theoretical and clinical importance, essentially, about the position of the analyst in the transference and the possibility of its handling in the clinic of the psychoses.